Total hip and knee replacement surgery results in changes in leukocyte and endothelial markers - Maclean Kirsty M; Edwards David R; Hendricks Beverly D; Hughes Stephen F; Bastawrous Salah S; Middleton Jim F (BMC, 2010)
Abstract Background It is estimated that over 8 million people in the United Kingdom suffer from osteoarthritis. These patients may require orthopaedic surgical intervention to help alleviate their clinical condition. Investigations presented here was to test the hypothesis that total hip replacement (THR) and total knee replacement (TKR) orthopaedic surgery result in changes to leukocyte and endothelial markers thus increasing inflammatory reactions postoperatively. Methods During this 'pilot study', ten test subjects were all scheduled for THR or TKR elective surgery due to osteoarthritis. Leukocyte concentrations were measured using an automated full blood count analyser. Leukocyte CD11b (Mac-1) and CD62L cell surface expression, intracellular production of H2O2 and elastase were measured as markers of leukocyte function. Von Willebrand factor (vWF) and soluble intercellular adhesion molecule-1 (sICAM-1) were measured as markers of endothelial activation. Results The results obtained during this study demonstrate that THR and TKR orthopaedic surgery result in similar changes of leukocyte and endothelial markers, suggestive of increased inflammatory reactions postoperatively. Specifically, THR and TKR surgery resulted in a leukocytosis, this being demonstrated by an increase in the total leukocyte concentration following surgery. Evidence of leukocyte activation was demonstrated by a decrease in CD62L expression and an increase in CD11b expression by neutrophils and monocytes respectively. An increase in the intracellular H2O2 production by neutrophils and monocytes and in the leukocyte elastase concentrations was also evident of leukocyte activation following orthopaedic surgery. With respect to endothelial activation, increases in vWF and sICAM-1 concentrations were demonstrated following surgery. Conclusion In general it appeared that most of the leukocyte and endothelial markers measured during these studies peaked between days 1-3 postoperatively. It is proposed that by allowing orthopaedic surgeons access to alternative laboratory markers such as CD11b, H2O2 and elastase, CD62L, vWF and sICAM-1, an accurate assessment of the extent of inflammation due to surgery per se could be made. Ultimately, the leukocyte and endothelial markers assessed during this investigation may have a role in monitoring potential infectious complications that can occur during the postoperative period.